Critic Analysis of Responsibility Practices of Waqf Institution: Reason Condition from Pondok Modern Darussalam Gontor - Syamsuri Syamsuri; Syamsuddin Arif; Alfarid Fedro; Vina Fithriana Wibisono (Universitas Darussalam Gontor, 2020)
Abstract Good waqf corporate management will contribute to the maximum achievement of waqf goals. Responsibility is one of the achievement of good waqf corporate management, however few waqf institutions cannot produce waqf assets due to lack of responsibility in management. This paper aims to analyze the practice of management responsibility in waqf institutions, evidenced by Pondok Modern Darussalam Gontor (PMDG) waqf management. This research is a field research with a qualitative approach. Data collection techniques using interviews, observation, documentation were analyzed with descriptive and thematic analysis. The result of the responsibility practice at PMDG intended for sustainability of independence education, namely; First, its waqf corporate management stands on official law in accordance with prevailed regulations. Second, the awareness of the responsibility of waqf governance, PMDG has implemented the vision, mission and objectives of the Gontor waqf charter as well as the application of Islamic corporate governance. Third, mapping waqf assets by producing various business units, expanding and utilizing land assets annually, and implementing the waqf motto that waqf must always move.Keywords: Waqf, Responsibility, Waqf Institution, Pondok Pesantren, Waqf Corporate Management. Abstrak Manajemen pengelolaan wakaf yang baik akan berkontribusi maksimal tercapainya tujuan wakaf. Tanggungjawab merupakan salah satu tercapainya pengelolaan korporasi wakaf yang baik, namun tidak sedikit institusi wakaf yang tidak bisa memproduktifkan asset wakaf dikarenakan oleh kurang terciptanya tanggungjawab dalam manajemennya. Tulisan ini bertujuan untuk menganalisis praktek responsibilitas manajemen dalam institusi wakaf, dibuktikan dengan fakta yang terjadi di Pondok Modern Darussalam Gontor (PMDG). Penelitian ini merupakan penelitian lapangan dengan pendekatan kualitatif. Teknik pengumpulan data menggunakan wawancara, observasi, dokumentasi yang dianalisis dengan deskriptif dan tematik analisis. Hasilnya adalah praktek prinsip tanggungjawab di PMDG bertujuan untuk mendorong keberlansungan kemandirian pendidikan melalui yaitu; pertama, pengelolaan wakaf berdiri di atas legal resmi sesuai dengan peraturan perudang-undangan yang berlaku. Kedua, dilihat dari kesadaran pertanggungjawaban tata kelola wakaf, PMDG telah menerapkan visi, misi dan tujuan piagam wakaf Gontor serta menerapkan manajemen korporasi islam. Ketiga, pemetaan aset wakaf yaitu dengan memproduktifkan berbagai unit-unit usaha, perluasan dan pemanfaatan aset tanah pertahunnya, serta menerapkan motto wakaf yaitu wakaf harus selalu bergerak.Kata Kunci: Wakaf, Responsibilitas, Institusi Wakaf, Pondok Pesantren, Manajemen Korporasi Wakaf.